2005
DOI: 10.1007/s00792-005-0435-6
|View full text |Cite
|
Sign up to set email alerts
|

Cis?trans isomerase gene in psychrophilic Pseudomonas syringae is constitutively expressed during growth and under conditions of temperature and solvent stress

Abstract: In a recent study, we established that psychrophilic Pseudomonas syringae (Lz4W) requires trans-monounsaturated fatty acid for growth at higher temperatures (Kiran et al. in Extremophiles, 2004). It was also demonstrated that the cti gene was highly conserved and exhibited high sequence identity with cti of other Pseudomonas spp. (Kiran et al. in Extremophiles, 2004). Therefore it would be interesting to understand the expression of the cti gene so as to unravel the molecular basis of adaptation of microorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
1
29
1
Order By: Relevance
“…In contrast to our data, most studies to date have suggested that pseudomonal CTIs are constitutively expressed (47). However, resistance to hydrocarbons, in particular toluene, has previously been linked with the isomerization of cis to trans FAs through an upregulation of CTI (up to 1.4-fold) in P. putida (48).…”
Section: Figcontrasting
confidence: 99%
“…In contrast to our data, most studies to date have suggested that pseudomonal CTIs are constitutively expressed (47). However, resistance to hydrocarbons, in particular toluene, has previously been linked with the isomerization of cis to trans FAs through an upregulation of CTI (up to 1.4-fold) in P. putida (48).…”
Section: Figcontrasting
confidence: 99%
“…P. syringae was mutagenized with a Tn5 transposon-based suicide plasmid vector (pOT182) (35,42), and cold-sensitive mutants were identified based on their inability to grow or their delayed growth on plates incubated at 4°C for 1 week. Growth characteristics were also analyzed using a UV-visible spectrophotometer (Shimadzu, Kyoto, Japan) (36,37).…”
Section: Generation Of Cold-sensitive Mutants Psychrophilic Pseudomomentioning
confidence: 99%
“…The disrupted gene was identified by inverse PCR (46) using 35 cycles and transposon-specific outward primers (primers Ash 1 and Ash 3 for upstream regions and primers Ash 1 and Ash 2 for downstream regions) ( Table 2). PCR-amplified products were purified and sequenced with a ABI Prism 3700 DNA sequencer (Applied Biosystems, California) (12,13,36,37) using Ash 1 and Ash 3.…”
Section: Generation Of Cold-sensitive Mutants Psychrophilic Pseudomomentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the predominant response of most bacteria to environmental perturbations is the alteration of the saturated/ unsaturated fatty acid ratio (Cronan & Gelmann, 1975;Ingram, 1976;Härtig et al, 1999;Ramos et al, 2002;Mrozik et al, 2004;Bisbiroulas et al, 2011;Paulucci et al, 2011). Other mechanisms, such as isomerization of cis/ trans double bonds (Gillan et al, 1981;Okuyama et al, 1991;Diefenbach et al, 1992;Heipieper et al, 2003;Bernal et al, 2007b;Kiran et al, 2005), shortening or elongation of fatty acid chain lengths (Cronan & Gelmann, 1975;Russell, 1984;Diefenbach et al, 1992) and changes in the ratio of terminally branched iso/anteiso fatty acids (Kaneda, 1977;Konopásek et al, 2000), have been found to play a role in the fluidity balance within bacteria. Modifications in the polar heads of anionic phospholipids have also been associated with the response to certain types of stress.…”
Section: Introductionmentioning
confidence: 99%